Three-dimensional arrangement of the capillary bed and its relationship to microrheology in the terminal villi of normal term placenta - Jirkovská, M; Janácek, J; Kaláb, J; Kubínová, L (Placenta, 2008)
Spatial arrangement of the capillary bed, manifestations of its growth and symmetry of capillary branching were studied in peripheral villi of normal human placenta at term using confocal microscopy and image analysis. Unlike the model that has been accepted so far, it was shown that the arrangement of the capillary bed in terminal villi varied from simple, U-like loops to a richly branched network. Three different categories of terminal villi (TV) were recognised: Signs of capillary elongation and sprouting were observed in the villous capillary bed. Based on the assessment of the mean cross-sectional areas of capillaries constituting simple, Y-like capillary bifurcation in terminal villi, the capillary branching was found to be asymmetric. Therefore, we conclude that the conditions for the "plasma skimming" effect are met in human placenta.
Keywords: Microscopy, Confocal; Pregnancy; reologie; kapiláry; mikrocirkulace; těhotenství; Placenta; Chorionic Villi; placenta; Capillaries; choriové klky; lidé; Female; Rheology; ženské pohlaví; Microcirculation; Humans; konfokální mikroskopie